Inovasi Teknologi Pembuatan Pakan Ayam Broiler Berbasis Bahan Baku Lokal - Mastur; Ashari; I K Sumadi; I GNG Bidura; Bulkaini (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The innovation of feed manufacturing technology is an innovation that can process pineapple peel waste into poultry feed by applying facultative anaerobic fermentation technology. The purpose of implementing this technological innovation is to optimize the use of several local raw materials (bran, milled corn and fermented pineapple peel) into poultry feed through the Partner Village Empowerment Program (PPDM) in 2021. This activity has been carried out in Sigar Penjalin Village in partnership with the group. youth mosque "Qomarul Huda Al-Hasanah" Cupek Hamlet. The method used in implementing the program is the Participatory Research Appraisal (PRA) method, which is a form of method that involves all members of the target partner in carrying out the work program. From the program that has been implemented, it is found that around 95% of the members of the mosque's youth group are ready to do business in the field of broiler chicken cultivation using feed sourced from local raw materials. The results of monitoring and evaluation show that the use of fermented pineapple peel can increase the slaughter weight of broiler chickens with a carcass percentage of 68.12%. The innovation of feed manufacturing technology is an innovation that can process pineapple peel waste into poultry feed by applying facultative anaerobic fermentation technology. The purpose of implementing this technological innovation is to optimize the use of several local raw materials (bran, milled corn and fermented pineapple peel) into poultry feed through the Partner Village Empowerment Program (PPDM) in 2021. This activity has been carried out in Sigar Penjalin Village in partnership with the group. youth mosque "Qomarul Huda Al-Hasanah" Cupek Hamlet. The method used in implementing the program is the Participatory Research Appraisal (PRA) method, which is a form of method that involves all members of the target partner in carrying out the work program. From the program that has been implemented, it is found that about 95% of the members of the mosque youth group are ready to do business in the field of broiler chicken cultivation using feed sourced from local raw materials. The results of monitoring and evaluation showed that the use of fermented pineapple peel can increase the weight of broiler chickens with a carcass percentage of 68.12%.